A Case of Paradoxical Embolism Causing Anterior Spinal Cord Syndrome and Acute Myocardial Infarction Following the Intradiscal Oxygen-Ozone Therapy - He, Runcheng; Huang, Qing; Yan, Xinxiang; Liu, Yunhai; Yang, Jie; Chen, Xiaobin (Frontiers in Neurology, 2019)
We report a case of a 66-year-old female who burst into flaccid paralysis of the lower extremities, accompanied by loss of pain and temperature sensation below T4 level, during an oxygen–ozone injection for disc herniation. Half an hour later, she suffered from chest pain. Magnetic resonance imaging (MRI) showed long segment hyperintensity in the thoracic spinal cord from T2 to 10 level on sagittal T2-weighted images (T2WI). The electrocardiogram (ECG) showed ST-segment elevation in V1–V6 leads. She was diagnosed with spinal cord infarction and ST-elevation myocardial infarction (STEMI). Transthoracic echocardiography with saline contrast showed existence of a large patent foramen ovale (PFO) correlating with the detection of massive microbubbles in the left atrium. We discuss the potential role of paradoxical embolism in spinal cord infarction and myocardial infarction.